The other radios: Alternative scenario in Peru - Rivadeneyra-Olcese, Carlos (2009)
Peruvian radio shows a huge diversity in direct proportion to its multiculturality, the same which shows a process full of different influences of social actor which have produced a complex and extremely rich scenario, that is also filled with opportunities and challenges. Beyond the great capital commercial radio are the other radios, small companies, provincial, from church or the mayor or small business owners sons of folkloric melomania, different actors with a passion to establish a new media. The multiple motivations produce a scenario with many types of radio that we wishes to start knowing.